2009
DOI: 10.1103/physrevlett.102.117001
|View full text |Cite
|
Sign up to set email alerts
|

Type-1.5 Superconductivity

Abstract: We demonstrate the existence of a novel superconducting state in high quality two-component MgB2 single crystalline superconductors where a unique combination of both type-1 (lambda{1}/xi{1}<1/sqrt[2]) and type-2 (lambda{2}/xi{2}>1/sqrt[2]) superconductor conditions is realized for the two components of the order parameter. This condition leads to a vortex-vortex interaction attractive at long distances and repulsive at short distances, which stabilizes unconventional stripe- and gossamerlike vortex patterns t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
328
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(349 citation statements)
references
References 28 publications
15
328
0
1
Order By: Relevance
“…It should be mentioned that this quest for new multiband superconductivity is a timely subject due to the possible emergence of nonmonotonic vortex-vortex interactions, a fingerprint of so-called type 1.5 superconductivity. [24][25][26] 174512-1 1098-0121/2013/88(17)/174512 (7) ©2013 American Physical Society…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that this quest for new multiband superconductivity is a timely subject due to the possible emergence of nonmonotonic vortex-vortex interactions, a fingerprint of so-called type 1.5 superconductivity. [24][25][26] 174512-1 1098-0121/2013/88(17)/174512 (7) ©2013 American Physical Society…”
Section: Introductionmentioning
confidence: 99%
“…Solving the variational problem for θ = εf (z) sin(q y y) andφ = εg(z) cos(q y y) [16], we can find the threshold (q y , µ) when the nematic state (2) is linearly unstable with respect to periodic distortions along the y-direction. The incompressibility of the smec- tic layers (4) implies that the linear correction to the level set function φ + εφ should satisfy ∇φ = ∇n, leading to:…”
Section: (3±1)·10mentioning
confidence: 99%
“…The richness of thermotropic liquid crystal (LC) phases [1], their susceptibility to external fields and their unique optical properties make LCs ideally suited to study symmetry breaking phase transitions. These transitions often involve the formation of isolated topological defects or complex ordered spatial structures (topological defect patterns) [2], with analogues in magnetism (grain boundaries, domain walls) [3], superconductivity (Abrikosov lattice, stripes) [4] and cosmology (cosmic strings, monopoles) [5]. Contrary to cosmological or quantum systems, LC patterns can be studied at room temperature using polarization microscopy, whence the formation, organization and kinetics of the defect structures can be fully explored.…”
mentioning
confidence: 99%
“…They found that mesoscopic confinement stabilizes the chiral states and in this state the vortex cores in different band condensates do not coincide, as well as fractional flux vortex states with broken time-reversal symmetry [19]. Many phenomena of interest are related to the difference in the healing lengths of the band condensates, being a possible [13,20]. In this work, we calculate the vortex state in a superconducting simple MgB 2 ceramic film exposed to a homogeneous magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in disks and square with structural defects and different boundary conditions were made to understand the vortex configurations and thermodynamics properties in mesoscopic samples. In these studies, it was found that the superconducting condensate is defined by the solutions of the time dependent linear Ginzburg-Landau (TDGL) equations [7][8][9][10][11][12][13][14]. Babaev et.…”
Section: Introductionmentioning
confidence: 99%